2017
DOI: 10.1002/alr.21989
|View full text |Cite
|
Sign up to set email alerts
|

Distinct histopathologic features of radiation‐induced chronic sinusitis

Abstract: Radiation-induced CRS patients exhibited greater squamous metaplasia and subepithelial edema when compared with a cohort of patients with CRSsNP, and decreased eosinophilia and basement membrane thickening compared with a cohort of CRSwNP patients. CRSr cases demonstrated no difference in eosinophilia or neutrophilia compared with CRSsNP, and decreased eosinophilia compared with CRSwNP, lending further credence to the unique nature of radiation in the development of CRS in this patient group. These findings ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 17 publications
4
48
0
Order By: Relevance
“…Epithelial sloughing, ciliary loss, intercellular and intracellular vacuolization, and ciliary dysmorphism were present in histologic examination of nasal epithelium after RT. Greater SM was also observed in histologic examination of nasal biopsied tissue from patients with CRSr compared to CRS patients without RT [18]. In this study, we demonstrated for the rst time that increased SM and expression of p63 + Krt5 + basal cells, together with loss of cilia and goblet cells, in nasal epithelium from patients with CRSr compared to both patients with CRSsNP and healthy controls.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Epithelial sloughing, ciliary loss, intercellular and intracellular vacuolization, and ciliary dysmorphism were present in histologic examination of nasal epithelium after RT. Greater SM was also observed in histologic examination of nasal biopsied tissue from patients with CRSr compared to CRS patients without RT [18]. In this study, we demonstrated for the rst time that increased SM and expression of p63 + Krt5 + basal cells, together with loss of cilia and goblet cells, in nasal epithelium from patients with CRSr compared to both patients with CRSsNP and healthy controls.…”
Section: Discussionsupporting
confidence: 56%
“…Radiation-induced mucositis is initiated by direct injury to epithelial cells and the underlying submucosal tissue [21]. Histologic examination of post radiation nasal tissue has shown increased brosis in the lamina propria, epithelial sloughing, ciliary loss, and intercellular and intracellular vacuolization, resulting in destruction of nasal epithelial barrier and subsequent epithelial remodeling [18]. In the present study, SM occurred more frequently in nasal epithelium from CRSr patients compared to CRSsNP patients without RT.…”
Section: Discussionmentioning
confidence: 42%
“…Structured histopathology allows the physician to profile a patient based on histopathologic features of disease without the burden of variability in phenotypic evaluation. Numerous previous studies have been reported utilizing this profiling methodology . To date, little is known regarding how histopathologic profiles affect CRS disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have been reported utilizing this profiling methodology. [9][10][11][12] To date, little is known regarding how histopathologic profiles affect CRS disease management. Oral corticosteroid utilization after FESS can provide insight into steroid necessity after surgery, and can potentially identify disease profiles that have increased steroid requirements postoperatively to control mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Cilia become more sparse and dysmorphic after radiation . Increased squamous metaplasia occurs in the sinonasal epithelium, along with reorganization to a stratified as opposed to pseudostratified columnar pattern, subepithelial edema, and increased collagen density in the lamina propria . Patients in turn develop sinus mucosal thickening and opacification, and clinical symptoms of CRS .…”
Section: Discussionmentioning
confidence: 99%